Smoking cessation support by text message during pregnancy: a qualitative study of views and experiences of the MiQuit intervention - Sloan, Melanie; Hopewell, Sarah; Coleman, Tim; Cooper, Sue; Naughton, Felix (Oxford University Press, 2017)
Introduction: SMS text messaging is increasingly used for delivering smoking cessation support and pilot studies suggest this may also be useful in pregnancy. This study explores the views of women who received a tailored text messaging cessation intervention (MiQuit) during pregnancy, focusing on acceptability, perceived impact, and suggestions for improvements.